Endovascular repair of aortic arch intramural hematoma and penetrating ulcers with 810 nm in situ laser‐assisted fenestration: Preliminary results of a single‐center. Issue 8 (7th May 2018) - Liu, Guang; Qin, Jinbao; Cui, Chaoyi; Zhao, Zhen; Ye, Kaichuang; Shi, Huihua; Liu, Xiaobing; Yin, Minyi; Yang, Guanglin; Huang, Sheng; Lu, Min; Huang, Xintian; et al.
Abstract : Purpose: The aim of the present study was to report the clinical outcomes of the use of 810 nm in situ laser‐generated fenestration (ISLF) for the treatment of aortic aneurysms (AAs) and intramural hematomas (IMHs) located in the aortic arch. Study Design and Methods: Between April 2014 and September 2017, 23 patients (15 men, mean age 66.0 years) with AAs ( n = 12) or IMHs ( n = 11) underwent thoracic endovascular aortic repair (TEVAR) with 810 nm ISLF of the arch. The primary outcomes of the safety assessment were the presence of endoleaks, mortality and morbidity, including adverse in situ fenestration‐related, cardiovascular, and cerebral events. Results: Technical success was achieved in all cases. Urgent intervention was performed in 15 (65.2%) cases. Left subclavian artery (LSA) ISLF was applied in six patients, LSA and left common carotid artery (LCCA) ISLF in three patients, and total aortic arch vessel ISLF in two patients. One patient suffered minimal stroke after the procedure and recovered without permanent disability to the extremities in 2 weeks. There were no fenestration‐related complications except in one patient with brachial artery access who suffered a hematoma and underwent incision repair at the puncture site. All fenestrations remained patent, and there were no endoleaks during a mean follow‐up of 10.5 ± 5.7 (range: 2–21) months. Conclusions: Complete or incomplete endovascular arch reconstruction by ISLF in arch diseases (AAs and IMHs) is feasible and reproducible with safe, effective, and favorable primary results and no need for customized endografts. Lasers Surg. Med. 50:837–843, 2018. © 2018 Wiley Periodicals, Inc.